2023
DOI: 10.1002/aenm.202203891
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling Electron‐ and Phase‐Transfer Processes to Enhance Electrochemical Nitrate‐to‐Ammonia Conversion by Blending Hydrophobic PTFE Nanoparticles within the Electrocatalyst Layer

Abstract: that could potentially reduce the reliance on the traditional fossil-fuel-based Haber-Bosch NH 3 production. [1] From a thermodynamic point of view, the electrochemical nitrogen reduction reaction (NRR) may benefit from a higher energy efficiency by about 20% than the Haber-Bosch process. [2] Nevertheless, achieving high-efficiency NRR is challenging due to the high dissociation energy of the NN bond (941 kJ mol −1 ) in N 2 and the low standard reduction potential (E°) of NRR (0.09 V vs RHE). As a result, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Figure 7a displays the typical electrocatalytic performance of TC 15 EMs on converting the nitrate under CFT and the control planar mode. It can be seen that TC 15 EMs convert almost all of NO 3 − -N (30 mg•L −1 , 100 mL) within 2 h under this flow-through mode, which is much more efficient than traditional planar catalysis. To evaluate well the catalytic capacity of TC 15 EMs, we also carried out the CFT experiments for 2 h under different concentrations of NO 3 − (Figure 7b).…”
Section: Electrocatalytic Performance Flow-by Electrocatalysismentioning
confidence: 91%
See 1 more Smart Citation
“…Figure 7a displays the typical electrocatalytic performance of TC 15 EMs on converting the nitrate under CFT and the control planar mode. It can be seen that TC 15 EMs convert almost all of NO 3 − -N (30 mg•L −1 , 100 mL) within 2 h under this flow-through mode, which is much more efficient than traditional planar catalysis. To evaluate well the catalytic capacity of TC 15 EMs, we also carried out the CFT experiments for 2 h under different concentrations of NO 3 − (Figure 7b).…”
Section: Electrocatalytic Performance Flow-by Electrocatalysismentioning
confidence: 91%
“…As one of the potential alternatives, the electrochemical routes of NH 3 synthesis have attracted widespread interest in recent years due to their mildness, sustainability, environment friendliness, and so on. , In particular, the electrochemical selective conversion of nitrate (NO 3 – ) ions, a widespread water pollutant, into valuable NH 3 or ammonia fertilizer is regarded as a win–win route for both resource recovery and pollution abatement . So far, most work in this area has targeted the development of electrocatalysts with improved properties, for example, the platinum group metals and copper-involved catalysts. Some work has focused on implementing ammonia separation and recovery by changing the configuration of the reaction system. Despite these advances, the traditional electrode configuration usually needs additional auxiliaries, which inevitably hinder the accessibility of the internal reaction activity sites and the efficient mass transport of electrolytes, making it difficult to fully exploit the performance of electrocatalysts, even those with high activity. Accordingly, it is necessary to explore some alternative strategies for improvements beyond those achievable by catalyst optimization alone. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as a green and sustainable solution, the use of electrocatalytic technology to upcycle polluting waste into high value-added chemicals is reliable. For example, the electroreduction process can convert NO 3 – into nontoxic nitrogen (N 2 ) or value-added ammonia (NH 3 ) under mild operating conditions. Notably, compared to the useless N 2 , NH 3 is largely needed as a basic raw material for various chemicals and an important carbon-free energy carrier. Meanwhile, the traditional NH 3 synthesis relies on the Haber–Bosch (H–B) process under high temperature and pressure operating conditions, resulting in serious environmental pollution and fossil energy consumption. On the contrary, the electrochemical nitrate reduction reaction (NO 3 RR) can achieve value-added ammonia production while treating nitrate wastewater, which is a win–win environmentally friendly process. In addition, the application of electrochemical oxidation in PET plastic waste upcycling can realize the conversion of EG from PET hydrolysate into value-added products (e.g., formate, glycolic acid (GA)). However, most of the previous reports have focused on the conversion of EG to formate (C1), and less on C2 products. As a biodegradable material with high mechanical strength, high biocompatibility, and rapid degradation, polyglycolic acid (PGA) plastics are widely used in biomedical fields. , Nevertheless, limited GA production and high prices have resulted in insufficient PGA production.…”
Section: Introductionmentioning
confidence: 99%
“…10 A local environment for the catalysts offering suitable hydrophobicity could reduce water adsorption and promote diffusion and affinity of the reagent to the electrode interface. 3,11 Creating a hydrophobic microenvironment for heterogeneous catalysis usually relies on external hydrophobic coatings, 12,13 making it challenging to control the local concentrations of reagents. Electro-driven hydrophobicity switches provide a reversible alternative that proved to be effective for catalysts with metal oxides and conjugate polymers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Creating a hydrophobic microenvironment for heterogeneous catalysis usually relies on external hydrophobic coatings, , making it challenging to control the local concentrations of reagents. Electro-driven hydrophobicity switches provide a reversible alternative that proved to be effective for catalysts with metal oxides and conjugate polymers. ,, Studies involving surfactants have shown that reversibility in those electroactive materials is possible .…”
Section: Introductionmentioning
confidence: 99%